IMPROVED STATISTICAL QCD MODEL FOR THE QUARK CONTENT of THE NUCLEON - Mirez, C. [UNESP]; Tomio, L. [UNESP]; Trevisan, L. A.; Frederico, T. (World Scientific Publ Co Pte Ltd, 2010)
The neutron-to-proton ratio of the structure functions, F(2)(n)/F(2)(p), as well as the corresponding difference F(2)(p)-F(2)(n) are obtained within a statistical quark model for the nucleon, where the quark energy levels are given by a central linear confining potential.
Keywords: Flavor symmetries; structure function; quark models